Rational load rating of deck-girder bridges with girder end shear cracks in reverse orientation - Bernica, Andrew (Kansas State University, 2016)
Reverse diagonal shear cracking at the supports of many reinforced concrete girders is a phenomenon affecting a number of KDOT’s low-volume bridges built in the early-to-mid 1900’s. This phenomenon is not addressed in the AASHTO Bridge Design Manual (2002) or ACI specifications. This study investigates the causes of this cracking and creates BRIDGE (Bridge Rating of Inclined Damage at Girder Ends), an Excel-based software to determine the load rating of a user specified bridge exhibiting reverse diagonal shear cracking at the girder supports. A user-interface is created which allows a user to create a grillage model of an existing bridge and to place various rating trucks on the bridge. Equivalent flexibility analysis is used to distribute the truck live loads from within the deck panels to the surrounding girders and diaphragms. Stiffness matrices are utilized to find the nodal displacements then the reactions at the girder supports caused by the truck live loads and bridge dead load. These reactions are checked against RISA software models to test the accuracy of the stiffness matrix application. ABAQUS FE models and Mohr’s circle stress distribution is used to find the driving and clamping forces on the crack. These forces are caused by resolving the dead and live load reactions and the friction force generated between the concrete girder and the rusty steel bearing pad along the shear crack orientation. These clamping and driving forces are used, along with the simplified modified compression field theory to determine the shear capacity of each girder at the reverse cracks. A modified version of Equation 6B.4.1 from the Manual for Bridge Evaluation (2011) is used to find the operating and inventory rating factors for the bridge.
Keywords: Load rating; Bridge; Shear cracking; Girder end